1997
DOI: 10.1097/00007632-199711150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Scoliosis That Develops After Pinealectomy in the Chicken and Comparison With Adolescent Idiopathic Scoliosis in Humans

Abstract: There are many similarities in the development of scoliosis in young chickens after pinealectomy and in children with adolescent idiopathic scoliosis. The few differences might be related to the different biomechanical properties associated with the spine in the two species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 6 publications
3
42
1
Order By: Relevance
“…Conversely, the results show that scoliosis was observed in 58% and 50% of groups B and C, respectively. Although Machida et al [19,20,21,23] have reported that 100% of their pinealectomized chickens developed a scoliotic curve, these results have not been confirmed in other studies [1,2,3,9,14,30,33,34]. Recently, a 52% incidence of scoliosis after pinealectomy was reported by Wang et al [34], and this is confirmed by the results of our current study.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Conversely, the results show that scoliosis was observed in 58% and 50% of groups B and C, respectively. Although Machida et al [19,20,21,23] have reported that 100% of their pinealectomized chickens developed a scoliotic curve, these results have not been confirmed in other studies [1,2,3,9,14,30,33,34]. Recently, a 52% incidence of scoliosis after pinealectomy was reported by Wang et al [34], and this is confirmed by the results of our current study.…”
Section: Discussioncontrasting
confidence: 58%
“…A review of the literature (Table 8) shows that, among the limited number of experimental studies of scoliotic deformity development following pinealectomy in chickens that have been published to our knowledge (including ours), all of them, except Machida et al [19,20,21,23] and Coillard and Rivard [9], demonstrated that scoliosis did not develop in all cases after pinealectomy in young chickens (2-3 days after hatching), even though serum MLT levels were significantly low [2,3,14,33,34]. Although there was no major difference in terms of definition of scoliosis, species of pinealectomized chicken or surgical pinealectomy technique among the studies, the observation period in these series ranged from 5 weeks to 32 weeks after pinealectomy, and the rate of experimentally induced scoliosis ranged from 52% to 100% [2,3,9,14,19,20,21,23,33,34]. The observation period was 12 weeks in the studies reported by Machida et al [19,20,21,23], but in those reported by Wang et al [33,34], Bagnall et al [2], and Beuerlein et al [3], it was only 5 weeks.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Early reports were of an incidence of scoliosis after pinealectomy that was as high as 100% [14]. Subsequent investigations have found the incidence to be as low as 50% [5,6,18,21,22,24]. Factors proposed to account for this difference includes: the age at which the surgery is performed [10], the structures resected at pinealectomy [4], and the length of follow-up [13].…”
Section: Introductionmentioning
confidence: 99%